Autopercepção de idosos do meio rural : um estudo com o Questionário de Saúde Geral-60 - Frighetto, Juliana (2014)
Studies in healthcare have been relevant on human aging by understanding the overall health, and, speaking with seniors about their reality and their perceptions becomes important. With seniors from rural context, it s necessary to pay attention to variables that may interfere with self-rated health. This study has the purpose of investigating the self-perceived general health, considering the gender variable. Data collection was performed with a stratified sample of 40 rural seniors without dementia. Cross-sectional study using a questionnaire as an instrument, the Geriatric Depression Scale - 15 and General Health Questionnaire. For quantitative analysis the SPSS18 was used, and qualitative analysis was guided by the theory of complexity of Edgar Morin. The results point to the importance of sex, because male seniors perceive themselves, statistically, with a bigger desire of dying, compared to female seniors. The study includes the fact that seniors that perceive themselves with gum problem perceive themselves with more sleep disorders. Moreover, the more one realizes of chronic diseases, the more rural seniors perceive their general health negatively. Low income was presented as a risk factor for death wish and felling with more or less confidence in their own performance, has to do with age. Self-perception of general health depends on the amount of drugs that seniors in rural areas take and the level of depression. This study comes to reinforce the importance of attending to the self-perception of seniors, aging in rural areas. Especially the male